Soil Degradation and its Challenges to Agricultural Production Resilience: an Overview from a Soil Traits Perspective - Indi Millatul Maula (Journal of World Science, 2026)
Soil degradation is a major problem that threatens the resilience of agricultural production due to the decline in the soil's ability to support sustainable plant growth. This study aims to examine soil degradation and its challenges to agricultural production resilience from the perspective of soil characteristics. The method used is literature review with a narrative review approach to previous research scientific articles. The literature analyzed is publications from the last ten years relevant to soil degradation, soil physical and chemical properties, and agricultural productivity. The results of the study show that the degradation of soil physical properties, such as compaction, structural damage, and erosion, as well as the degradation of soil chemical properties, especially the decline of organic matter and nutrient imbalances, have a significant effect on the decline and instability of agricultural production. The literature synthesis confirms that soil degradation is a strategic challenge in maintaining the long-term resilience of agricultural production. Therefore, a soil quality-based approach is needed to support the sustainability of agricultural systems.